Collaborative Strategic Model of Creative Economy Actors and the Halal Industry in Accelerating International Market Penetration in Pekalongan - Salma Nabila; Moses Adeolu AGOI; Kuat Ismanto (Yayasan Abdurrauf Cendekia Nusantara, 2026)
The global halal industry has shifted towards fashion, offering vast opportunities for Pekalongan's creative economy. However, despite its status as a UNESCO Creative City, the export of Pekalongan's creative products (crafts and batik) is hindered by MSMEs' low literacy regarding halal value chain standards and critical contamination risks during production. Previous studies have mostly treated the creative economy and halal industry separately, leaving a significant gap in integrative frameworks. Addressing this research gap, this study aims to construct a strategic collaboration model among stakeholders to overcome these export barriers. Using an exploratory qualitative case study method, primary data were gathered through in-depth interviews with key Pentahelix elements—namely government, academia, business, community, and media. The results indicate that integrating comparative cultural advantages with competitive halal compliance through the Pentahelix model triggers value co-creation. This synergy empowers the government as a regulatory catalyst, academia in material innovation, businesses as export aggregators, communities as ethical supervisors, and media for digital branding. This collaboration fosters the